EFEKTIVITAS PELAKSANAAN DIVERSI TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (Studi Kasus Di Wilayah Hukum Kepolisian Resort Donggala) - Muliadi Muliadi; Imam Basofi Usman (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
Article 28 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia (hereinafter abbreviated as the 1945 Constitution of the Republic of Indonesia) states that children have a strategic role and the state guarantees the rights of every child to survival, growth and development and protection from violence and discrimination . Contact with the criminal justice system is the starting point for children facing the law. The term criminal justice system describes a legal process that is applied to someone who commits a crime or violates the suitability of criminal law. The aim of the study was to determine the effectiveness of the diversion of children facing the law at the Donggala Resort Police as well as the obstacles faced in implementing diversion against children facing the law. The long-term goal to be achieved is the realization of the diversion of children facing the law at the Donggala Resort Police. The specific target to be achieved in this study is so that investigators, especially PPA investigators, Donggala Resort Police can be maximal in resolving cases of children facing the law. The research method used in this study is to use a type of normative-empirical research or also called sociological legal research (non-doctrinal). Keyword : Diversion, Effectiveness, Children